Endodontic and dental practice during COVID-19 pandemic: Position statement from the Indian Endodontic Society, Indian Dental Association, and International Federation of Endodontic Associations - Jogikalmat Krithikadatta; Ruchika Roongta Nawal; Kurinji Amalavathy; William McLean; Velayutham Gopikrishna (Wolters Kluwer Medknow Publications, 2020)
The emergence of COVID-19 pandemic poses an immense global health challenge. As dental care providers, we are faced with significant responsibilities both to the dental team and our patients to limit exposure to the virus. Due to the nature of our work, the team are at a high risk of contracting the virus and potentially transmitting the virus. One of the prime modes of containing this pandemic is in enforcing effective social distancing. However, as dental care providers, we face the twin challenge of protecting ourselves and our patients from community transmission and at the same time ensuring patients continue to have access to urgent/emergency dental care. This position statement is for the benefit of endodontists and dentists and provides an objective method of streamlining their dental practices based on need and evidence-based disease containment protocols.